New records of red algae (Rhodophyta) for Cabezo Reef, National Park Sistema Arrecifal Veracruzano, Gulf of Mexico - Galicia-García, Citlalli; Robinson, Néstor M.; Okolodkov, Yuri B. (Instituto de Ecología, A.C., 2013)
Descriptions of 21 red algal species collected in March and November 2008 and June 2010 are given. They are considered new records for Cabezo reef in the southeastern part of the National Park Sistema Arrecifal Veracruzano (NPSAV), southwestern Gulf of Mexico. The new records belong to the genera Amphiroa, Bryothamnion, Ceramium, Ceratodictyon, Colaconema, Galaxaura, Hypnea, Jania, Laurencia, Liagora, Neosiphonia, Pneophyllum, Polysiphonia, Porolithon, Stylonema, Titanophycus and Yuzurua. The families Rhodomelaceae and Corallinaceae contain the largest number of species (6 and 5, respectively). Descriptions include morphometric and biological data and are accompanied by photographs and line drawings for each species. Geographic distribution of these algae in the State of Veracruz, park and the Gulf of Mexico are also provided. Polysiphonia pseudovillum is a new record for the Gulf of Mexico, while Colaconema hallandicum and Ceratodictyon planicaule are new records for the park. Nine species have been found as epiphytes mainly on green and red algae. Tetrasporangia were the dominant reproductive structures found in the studied species during both rainy and dry seasons. Vegetative and reproductive thalli of 10 species from the NPSAV were usually smaller compared to those of the same species found in the Caribbean.